Learning Geography Beyond the Traditional Classroom Examples from Peninsular Southeast Asia - Chang, Chew-Hung; Wu, Bing Sheng; Seow, Tricia; Irvine, Kim (Springer Nature Singapore : Imprint: Springer, 2018)
X, 214 p. 50 illus.